Digitalisasi Marketing Sebagai Strategi dalam Meningkatkan Penjualan UMKM Kuliner di Cafe Uniang Pasca Pandemi Covid - 19 : GOFOOD DAN SHOPEEFOOD - Aswin, Ullya Rahmi; Gustina , Leni; Dianti, Muthia Rahma (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Community Service is a form of the Tridharma of Higher Education. This PKM is proposed to carry out activities that are socialization of digital product marketing post Covid-19 pandemic. Covid-19 pandemic impact turnover decrease and limited consumers, cause restrictions on interactions between producers and consumers, especially in Putra Indonesia University (YPTK) Padang campus. Jl Aru RT 04 RW 09 in Lubuk Begalung has a significant culinary business development and near on the campus of UPI YPTK Padang. The pandemic situation had a major impact on the development of Culinary cause learning activities through online classes. If this happens continuously without anticipation, the culinary business will suffer losses. So there must a strategy for SME’s to survive in the face of new habits. The use of digital media is an alternative for SME’s to survive along pandemic. The aim of this community service is increasing the knowledge and skills of Culinary Entrepreneurs, so they can implement more effective and efficient digital marketing strategies. The service method is a training. The training stages are divided into 4 (four) stages, there are preparation stage, implementation stage, program evaluation stage and reporting stage. The expected results are to increase the knowledge, understanding, and skills of culinary entrepreneurs regarding how to determine and implement digital marketing strategies more effectively and efficiently for their culinary products.